Sistem Pendukung Keputusan Pemilihan Bibit Unggul Ikan Lele Menggunakan Metode Analytical Hierarchy Process (AHP) - Fani Setiawan; Iwan Giri Waluyo (CV. Multi Kreasi Media, 2023)
In determining the quality of catfish seeds that are in a catfish farm, the farmer wants to make a selection for the selection of superior catfish seeds. The breeder still uses a manual system or method to determine catfish seeds so that it is less accurate in determining which seeds are superior. Therefore, the authors designed a Decision Support System based on a method that will be used later. That is utilizing the Analytical Hierarchy Process (AHP). One approach to determining the degree of need for relevant rules and having a value for computational consistency is this method is quite simple to be applied in the process of selecting superior catfish seeds in catfish farms independently. This Decision Support System will greatly assist farmers in recognizing superior catfish seeds quickly and accurately.